CURRENT ADMINISTRATIVE LAW FORMATION IN UKRAINE: LAW DISCOURSE - Sinyuta , Людмила Леонтьевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
Attention is paid to lack of correspondences of the administrative law notions with achievements of legal science. Key issues that should be solved are the following: place of the administrative law in the system of law, the system of administrative law itself and qualitative contents of the administrative law.